Two Adult Siblings With Myotonic Dystrophy Type 1 With Different Phenotypes Presenting With Chronic Respiratory Insufficiency and Sleep Apnea Syndrome - Kohno, Genta; Ogawa, Katsuhiko; Kushimoto, Masaru; Tanaka, Sho; Ikeda, Jin; Nishizawa, Tsukasa; Mitsuke, Kazutaka; Nakayama, Tomohiro; Suzuki, Yutaka; Ishihara, Hisamitsu; Fujishiro, Midori (Frontiers in Neurology, 2019)
Myotonic dystrophy type 1 (DM1) is an autosomal dominant disease characterized by progressive muscle weakness and myotonia along with multiple organ system involvements. Overall, DM1 patients show reduced life expectancy, mainly due to respiratory or cardiac abnormalities. Chronic respiratory impairment is associated with increased morbidity in DM1. The main ventilatory dysfunction etiology in DM1 is complex, consisting of both peripheral respiratory dysfunction and central respiratory drive dysfunction as well as upper airway muscle dysfunction leading to obstructive sleep apnea syndrome (SAS) and aspiration. Advancements in early diagnosis of DM1 and management with non-invasive therapeutic tools have improved life expectancy for DM1 patients. We present herein two siblings with DM1, a thin elder brother and an obese younger sister with visceral fat accumulation. Although neither had voluntary symptoms related to respiratory dysfunction, their apnea-hypopnea indices revealed severe SAS and subsequent arterial blood gases studies showed hypercapnia as well as hypoxia, suggesting central nervous system involvement with peripheral respiratory dysfunction. Noninvasive positive pressure ventilation during sleep was started following pulmonary assessment. Respiratory function should be assessed in DM1 patients, even those free of respiratory symptoms, because respiratory muscle weakness occurs in a high percentage of these patients and will shorten their lives.